Evaluation of the antibacterial and antibiofilm effect of mycosynthesized silver and selenium nanoparticles and their synergistic effect with antibiotics on nosocomial bacteria - Nahed Fathallah Fahmy; Marwa Mahmoud Abdel-Kareem; Heba A. Ahmed; Mena Zarif Helmy; Ekram Abdel-Rahman Mahmoud (Microbial Cell Factories)
Abstract Background The healthcare sector faces a growing threat from the rise of highly resistant microorganisms, particularly Methicillin-resistant Staphylococcus aureus (MRSA) and multidrug-resistant Pseudomonas aeruginosa (MDR P. aeruginosa). Facing the challenge of antibiotic resistance, nanoparticles have surfaced as promising substitutes for antimicrobial therapy. Recent studies showcase the effectiveness of various fungi species in nanoparticle synthesis. Mycosynthesized silver nanoparticles (AgNPs) and selenium nanoparticles (SeNPs) using Aspergillus carneus MAK 259 has been investigated and demonstrate antibacterial, antibiofilm and synergistic activities against (MRSA) and (MDR P. aeruginosa). Results In the current research, silver nanoparticles (AgNPs) and selenium nanoparticles (SeNPs) were produced extracellularly using A. carneus MAK 259 culture supernatants. Colour change, an initial evaluation of the production of AgNPs and SeNPs. Then, UV absorption peaks at 410 nm and 260 nm confirmed the production of AgNPs and SeNPs, respectively. AgNPs and SeNPs were dispersed consistently between 5‒26 nm and 20–77 nm in size, respectively using TEM. FT-IR analysis was used for assessing proteins bound to the produced nanoparticles. The crystallinity and stability of AgNPs and SeNPs was confirmed using X-ray diffraction analysis and zeta potential measurements, respectively. Antibacterial, antibiofilm and synergistic effects of both (NPs) with antibiotics against MRSA and MDR P. aeruginosa were tested by Agar well diffusion, tissue culture plate and disc diffusion method respectively. Both (NPs) inhibited the growth of P. aeruginosa more than S. aureus. But, SeNPs was stronger. AgNPs had stronger antibiofilm effect especially on biofilms producing S. aureus. as regard synergestic effects, Both (NPs) had higher synergestic effects in combination with cell wall inhibiting antibiotics against P. aeuroginosa While, on S. aureus with antibiotics that inhibit protein synthesis and affect metabolic pathways. Conclusions Our study demonstrated that the mycosynthesized SeNPs had remarkable antibacterial effect while, mycosynthesized AgNPs exhibited a considerable antibiofilm effect. Both NPs exhibited higher synergistic effect with antibiotics with different modes of action. This approach could potentially enhance the efficacy of existing antibiotics, providing a new weapon against drug-resistant bacteria where the described silver and selenium nanoparticles play a pivotal role in revolutionizing healthcare practices, offering innovative solutions to combat antibiotic resistance, and contributing to the development of advanced medical technologies.